Power Relations in Partnership Practices in the Education Sector: Case Study of State Vocational High School 2 Yogyakarta. - Fatkhurrohman, Mochammad; Rosyari, Fandi Rizki (Universitas Brawijaya, 2020)
This research aims to see the power relations between the school, industry and society or students in the practice of partnerships in the education sector. The partnership seeks to involve the community, both in groups and individually. In a partnership there is a relationship between organizations and with that relationship cooperation will be created. Each of these actors has varying interests, expertise, resources and decision-making abilities. Therefore, it is very interesting to see how the negotiation process takes place between actors. Whether each actor managed to get his interests. This research is a descriptive qualitative research using a case study approach. In this study, researchers will develop concepts and gather facts that can answer questions in the formulation of the problem by looking at the rationality of each actor involved in the practice of partnership in SMKN 2 Yogyakarta. Researchers will use in-depth interviews with several informants to obtain accurate data. The results of this study are both the school, industry and society or students have rationality in undergoing this partnership. They use the rationality in the negotiation process to determine the types of partnerships. Although each actor has succeeded in fulfilling his interests, in reality there are still actors who get greater benefits. This shows the dominant pattern of relations. There are two things that led to the emergence of the relation pattern, the rules made by the Government and the resources owned by each actor offered during the negotiation process.